2004
DOI: 10.1074/jbc.m409307200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Protein-Protein Interactions between MutL and MutH by Cross-linking

Abstract: Strand discrimination in Escherichia coli DNA mismatch repair requires the activation of the endonuclease MutH by MutL. There is evidence that MutH binds to the N-terminal domain of MutL in an ATP-dependent manner; however, the interaction sites and the molecular mechanism of MutH activation have not yet been determined. We used a combination of site-directed mutagenesis and site-specific cross-linking to identify protein interaction sites between the proteins MutH and MutL. Unique cysteine residues were intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 35 publications
5
80
0
Order By: Relevance
“…However, in the absence of ADPnP, TmL bound to ssDNA with an apparent KD value of 53.75 ± 5.32 nM and, in the presence of ADPnP, exhibited a higher KD of 25.65 ± 8.47 nM, with a relatively high error-range. These KD values were larger than those form previous E. coli MutL studies (10), but the present results were consistent with previously reported data regarding the ability of bacterial MutL to bind ssDNA in the presence of nucleotides (10,12,13).…”
Section: Tml and Its Mutants Had Ssdna Binding Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the absence of ADPnP, TmL bound to ssDNA with an apparent KD value of 53.75 ± 5.32 nM and, in the presence of ADPnP, exhibited a higher KD of 25.65 ± 8.47 nM, with a relatively high error-range. These KD values were larger than those form previous E. coli MutL studies (10), but the present results were consistent with previously reported data regarding the ability of bacterial MutL to bind ssDNA in the presence of nucleotides (10,12,13).…”
Section: Tml and Its Mutants Had Ssdna Binding Propertiessupporting
confidence: 93%
“…Homodimeric interactions at the N-terminal region of E. coli MutL has been previously shown and single-cysteine E. coli MutL variants found to be crosslinked with the bifunctional linkers bis-maleimidoethane and 1,11-bis-maleimidotetraethyleneglycol, both in the presence and absence of nucleotides (13). A crosslinking assay of the E. coli MutL and its N-terminal domain showed that incubation with ADPnP affects its conformational changes and multimerization (11).…”
Section: Tml Displayed Nucleotide-and Ssdna-dependent Conformational mentioning
confidence: 93%
“…These models were filtered using the experimentally derived distance constraints (this work and Ref. 37). For details of the procedure, see the supplemental information.…”
Section: Methodsmentioning
confidence: 99%
“…For cross-linking experiments with BMOE, 200 l of membrane samples adjusted to 1 g of protein/l were mixed with BMOE at a final concentration of 0.4 mM at 37°C or room temperature. At different time points, 20-l aliquots were withdrawn, and the reaction was quenched by addition of DTT to a final concentration of 50 mM and further incubation for 15 min (Giron-Monzon et al, 2004). Samples were analyzed by SDS-PAGE under nonreducing conditions.…”
Section: Cyp2c8 Membrane Organizationmentioning
confidence: 99%